The outsiders - Hinton, S. E. (London : Puffin Books, 2007)
The struggle of three brothers to stay together after their parent's death and their quest for identity among the conflicting values of their adolescent society.
Notable/Best Books (A.L.A.).
Wilson's Junior High School.
Wilson's Senior High School.
5.1
Young Adult
Keywords: Brothers -- Fiction; Family life -- Fiction; Gangs -- Fiction